Establishing an objective biomarker for corneal cystinosis using a threshold‐based Spectral domain optical coherence tomography imaging algorithm. Issue 2 (24th August 2020) - Keidel, Leonie; Elhardt, Carolin; Hohenfellner, Katharina; Priglinger, Siegfried; Schworm, Benedikt; Wertheimer, Christian; Priglinger, Claudia; Luft, Nikolaus
Abstract: Purpose: The purpose of the present study was to establish a semi‐automated threshold‐based image segmentation algorithm to detect and objectively quantify corneal cystine crystal deposition in ocular cystinosis with anterior segment optical coherence tomography (AS‐OCT). Methods: This prospective, observational, comparative study included 88 eyes of 45 patients from the German Cystinosis Registry Study as well as 68 eyes of 35 healthy control subjects. All eyes were imaged with AS‐OCT (Cirrus HD‐OCT 5000, Carl Zeiss Meditec AG, Jena, Germany). As an initial step, B‐scan images were subjectively analysed for typical changes in morphology in comparison to healthy controls. Based on the experience gained, an objective semi‐automated B‐scan image segmentation algorithm was developed using a grey scale value‐based threshold method to automatically quantify corneal crystals. Results: On AS‐OCT B‐scans, corneal crystals appeared as hyperreflective deposits within the corneal stroma. The crystals were distributed either in all stromal layers (43 eyes, 49%) or confined to the anterior (23 eyes, 26%) or posterior stroma (22 eyes, 25%), respectively. The novel automatic B‐scan image segmentation algorithm was most efficient in delineating corneal crystals at higher grey scale thresholds (e.g. 226 of a maximum of 255). Significant differences in suprathreshold grey scale pixels were observable between cystinosis patients and healthy controls (p < 0.001). In addition, the algorithm was able to detect an age‐dependent depth distribution profile of crystal deposition. Conclusion: Objective quantification of corneal cystine crystal deposition is feasible with AS‐OCT and can serve as a novel biomarker for ocular disease control and topical treatment monitoring.